Analysis of Biocharcoal Briquette Characteristics with the Addition of Trembesi (Samanea saman) Dry Leaf Bioadditives - Hidayat, Muhamad Farhan; Muhaji, Muhaji; Abdullah, Muhamad Yunus (Journal of Mechanical Engineering, Science, and Innovation, 2024)
Biocharcoal briquettes are new and renewable biomass energy products. The addition of rain tree leaf bioadaptive to biocharcoal briquettes can increase high carbon compounds. By adding these materials, it can increase the calorific value and produce better energy. The main ingredients in this study were coconut shells, corn cobs, tapioca flour, and betel leaf bioadditives. The research characteristic test was conducted to determine the levels of bound carbon, ash content, volatile matter content, calorific value, and water content. The results showed that the best composition was BBB 4 with a volatile matter content of 0.921%, water content of 2.0%, ash content of 7.9%, calorific value of 5943 cal/g, and bound carbon of 89.179%.